Collaborative design of Older Women ' s CoHousing. Issue 4 (14th December 2015) - Devlin, Patrick; Douglas, Rachel; Reynolds, Tom
Abstract : Purpose: – CoHousing provides a new approach in the UK to older people's housing, and meets a clear demand for similarly minded groups of individuals who would like to grow old together. The purpose of this paper is to explore how a Collaborative Design Process (CDP) can work, as applied to a soon-to-be realised project in North London. Design/methodology/approach: – Report by the architects with comment from an end user on a CDP including end users, architect, developer and housing association management. Findings: – A group of individuals that has invested in building decision-making capacity can participate meaningfully in the design of their future homes. Research limitations/implications: – This research was focused on one development, so work on a wider range of projects would help test its validity. Social implications: – Older Women's CoHousing (OWCH), and similar projects, demonstrate an appetite for: mutually supportive, intentional communities; planned downsizing and contemporary, sociable design for the third age of life. Originality/value: – The CDP developed for OWCH was comprehensively documented. It has already been adapted for further cohousing developments, and is intended to continue to evolve with the demands made on it.